The state of patient-dentist communication among the adult population of Ukraine - Barkovska, Anastasiia; Kostenko , Viktoriia (The Ukrainian Scientific Medical Youth Journal, 2023)
effective communication between patients and dental doctors is a critical component in providing high-quality dental care and preserving overall health. Unknown terms and insufficient health-related information can lead to a misperception of the disease, diagnosis, and treatment processes that, in turn, may result in more serious health consequences. Therefore, it is essential to pay attention to the quality of patient-dentist communication in order to prevent dental anxiety and dental fear, which induces patients to avoid dental visits and, in general, reduces the effectiveness of treatment, makes any preventive measures impossible to implement. The objective of this study is to determine the level of dental anxiety, understanding of information provided at the dentist’s, and to assess the impact of unknown technical vocabulary in the dentist's speech on patient-doctor communication among Ukrainians aged 20 – 39. The study was conducted using an anonymous survey of 200 respondents aged from 20 to 39, including 151 women and 49 men. The survey consisted of 20 questions, 5 of which were adapted from the Modified dental anxiety scale (MDAS), other were formulated by the authors. The findings obtained were analyzed using STATISTICA for Windows 13 software (StatSoft Inc., # JPZ804I382120ARCN10-J). It was found that dental anxiety is prevalent in nearly half of the adult population in Ukraine, particularly among women and individuals aged 20-29. 55.4% of the respondents feel anxious at the dentist’s appointment because of special technical words, while 38.4% of them gain credence. As people age, they are more likely to consider that unclear words have no impact on communication. The term `anesthesia` is the most understandable among those researched, while the term `endodontic treatment` was unclear to 62.7% of respondents, especially among those aged 30-39 and women. Men are more likely to interpret the term as `painful procedure`. The term `cyst` is considered curable with the tooth preservation more often than with its necessary removal - 20.8% vs. 6.8% of all respondents respectively. Beliefs about the impossibility of saving a tooth are more common among people aged 20-29 - 9.2% vs. 5.9% of people aged 30-39. The difference in number of male and female respondents who consider that `benign neoplasm` `must be removed` depends on age: in the 20-29-year-old group, the `must be removed` option prevailed among men - 30.8% vs. 25.4% of women; in the 30-39 age group - prevailed among women - 43.2% vs. 23.1% of men. To conclude, dental anxiety is prevalent in nearly half of Ukrainian adults, particularly among women and individuals aged 20-29. Dental technical words are found as eliciting more anxiety than trust or fear, but this effect decreases with age, as more Ukrainians consider that technical words do not have a significant impact on further communication between the dentist and patient. Dentists are advised to avoid such terms as `endodontic treatment` and use their analogues, or to make sure that the patient fully comprehends the information provided in order to prevent misunderstandings and dental anxiety level growth.